PENGARUH GREEN MARKETING DAN TERHADAP PURCHASE DECISION (Studi pada Generasi Z dalam Pembelian Green Skincare Product Brand The Body Shop dan Sensatia Botanicals) - Dirgantari, Puspo Dewi; Fajri, Fadilla Nur; Widjajanta, Bambang (Business Education Program of Universitas Pendidikan Indonesia, 2022)
The increasing number of competitors in Skincare Industry, requires companies to strengthen marketing strategies in creating Purchase Decision. Green marketing is a strategy that can contribute to building Purchase Decision for Green Skincare Product. This study was to analyze the significance of The Influence of Green Marketing on Purchase Decision. The population in this study were Generation Z who used Green Skincare Product Brand The Body Shop dan Sensatia Botanicals in Indonesia with a sample of 200 people. The sampling technique used purposive sampling. The analysis technique used is Structural Equation Modeling (SEM) analysis with IBM SPSS AMOS 23.0 for Windows program. The results of this study indicate that the description of Green Marketing (green product, green price, green place,and green promotion) as varible (X) has a significant effect on purchase decisions as Variable (Y). The green product dimension in green marketing gives the biggest contribute to building purchase decision.Keyword: Generation Z, Purchase Decision, Green Marketing, Green Skincare ProductsSemakin banyaknya pesaing di Industri Skincare, menuntut perusahaan untuk memperkuat strategi pemasaran dalam menciptakan Keputusan Pembelian. Green Marketing merupakan strategi yang dapat berkontribusi dalam membangun Keputusan Pembelian Produk Green Skincare. Penelitian ini bertujuan untuk menganalisis signifikansi Pengaruh Green Marketing terhadap Keputusan Pembelian. Populasi dalam penelitian ini adalah Generasi Z yang menggunakan Produk Green Skincare Brand The Body Shop dan Sensatia Botanicals di Indonesia dengan sampel sebanyak 200 orang dengan teknik pengambilan sampel menggunakan purposive sampling. Teknik analisis yang digunakan adalah analisis Structural Equation Modeling (SEM) dengan program IBM SPSS AMOS 23.0 for Windows. Hasil penelitian ini menunjukkan bahwa deskripsi Green Marketing (green product, green price, green place, dan green promotion) sebagai variabel (X) berpengaruh signifikan terhadap keputusan pembelian sebagai Variabel (Y). Dimensi green product dalam Green Marketing memberikan kontribusi terbesar dalam membangun keputusan pembelian.Kata kunci : Generasi Z, Purchase Decision, Green Marketing, Green Skincare Products